How to avoid household debt overhang? An analytical framework and analysis for India - Naoyuki Yoshino; Prachi Gupta (Asian Development Bank Institute (ADBI), 2019)
In this paper we develop an analytical framework using the household utility maximization approach to model stability conditions to avoid household debt overhang. Our theoretical framework suggests that household debt stability is a function of five factors, namely the rate of interest, period of lending, income growth, loan-to-income ratio, and households' disutility from borrowing parameter. Further, we apply our analytical model to the case of India and estimate household debt stability conditions for Indian households under various scenarios to estimate the ceiling borrowing ratios borrowing below which households can avoid the risk of running into a debt overhang problem.
Keywords: C13; C15; C62; D10; H31; 330; debt overhang; household finance; household borrowing